Egressos dos cursos superiores de licenciatura : mobilidade social ou geração enganada? : um estudo de caso na Universidade Federal da Fronteira Sul - Campus Erechim/RS - Mikolaiczik, Daniê Regina (2022)
The social mobility provided by education, in a country marked by structural inequalities, is still multifaceted, as it can vary according to factors such as color, sex, type of institution of schooling of each graduate, among others. Based on this finding, the present dissertation adopted as a general objective to understand the nuances of social mobility provided, or not, by the degree of the undergraduate degree. It started with the question: “What is the impact of the diploma on the social mobility of the graduate?”. The research was characterized by a case study aimed at investigating a public university located in the North Region of Rio Grande do Sul, the Federal University of Fronteira Sul – Erechim/RS campus. The operationalization of this case study took place through a quantitative-qualitative approach, involving the collection of data through questionnaires, with open and closed questions, among the graduates of six undergraduate courses at the institution. Social mobility was analyzed in the light of Pierre Bourdieu's theory and it was evaluated whether there was a transformation in the cultural, economic, social and symbolic capital of the participants. In the context of the case study, it was found that, for the 102 graduates of higher teacher training courses who answered the questionnaire, social mobility occurred in parts, since cultural and social capital were significantly impacted by the completion of the course, while capital economic and symbolic have undergone more discreet changes. The content analysis of the open question showed that graduates recognize the role of the public university in transforming their lives, but still find it difficult to enter the job market and face the devaluation and precariousness of the teaching profession. It was concluded from this research that, in the context studied, the democratization of higher education facilitated the entry of the popular classes to the university, however, in higher education courses, the possibilities of social mobility are still fragile. The study showed that the challenge of the real democratization of Brazilian higher education goes beyond access, as it involves the offer of a diploma that provides a dignified life, as well as professional and salary appreciation, combined with the perspective of cultural and personal growth.